Koncesije na področju zdravstvene dejavnosti - Mužina, Aleksij (Podjetje in delo, 2020)
According to the authors, Article 41 of ZZDej-K represents an arbitrary intervention into existing healthcare concessions in Slovenia that is contrary to some fundamental rights guaranteed by the Constitution in Art. 2 (the rule of law), Art. 33 (the right to private property), Art. 51 (the right to health care), Art. 155 (interdiction of retroactivity), and Art. 158 (finality of legal decisions).
Keywords: concession; health care; healthcare; koncesije; medicina in pravo; physicians; zdravstvena dejavnost; zdravstvo; ZZDej